Binary Biosorption of Cu(II) and Cr(VI) by Sawdust - Salamah Lutfi Ni’matus; Pinem Yoga Dinarta; Andi Kurniawan (Postgraduate School Universitas Brawijaya, 2022)
Water pollution is one of many significant environmental problems. One of the sources of pollutants that become a problem in the aquatic environment is the heavy metals Cu(II) and Cr(VI), whose presence can harm living things, including humans. Therefore, a technology is needed to overcome Cu(II) and Cr(VI) pollution. Biosorption is one of the technologies offered to overcome these problems with several advantages, namely cost-effectiveness and environmentally friendly. This study investigated the biosorption of Cu(II) and Cr(VI) using sawdust. The use of sawdust was chosen because it is easy to find and the price is affordable. This study's results indicate that sawdust can adsorb Cu(II) and Cr(VI). The optimum contact time for biosorption in this study was 5 minutes. The biosorption characteristics shown in this study matched the Langmuir adsorption model. This study shows that the biosorption of Cu(II) and Cr(VI) by sawdust occurs through physicochemical reactions, ion exchange, and electrostatic interactions. Therefore, sawdust is one of the promising biosorption agents to overcome pollution in aquatic ecosystems, especially pollution caused by Cu(II) and Cr(VI). Keywords: biosorption, aquatic ecology, cu(ii), cr(vi), sawdust, water pollution